Development of Smart Blocks for Cognitive Rehabilitation of Patients with Dementia - An, Jea-Yong; Lee, Seok; Oh, Junhyeok; Lim, Tae Yoon; Jang, Seonghoon; Hwang, Jun Ho; Woo, Deok Ha; Shin, Jeong Hun; Kim, Ki Woong; Han, Ji Won; Suh, Seung Wan; Han, Ji Hyun; et al. (PROCEEDINGS OF TENCON 2018 - 2018 IEEE REGION 10 CONFERENCE, 2018)
The increase in the elderly population increases the incidence of geriatric diseases such as cancer, stroke, heart disease, and dementia. Cognitive impairment and a debilitated memory ability decreases the quality of life of patients owing to the associated economical and physical problems, and increases the burden on their family. The impairment of cognitive function due to dementia can be reduced through repeated and systematic training; however, this process can lead to disinterest and loss of concentration. Toys can stimulate various parts of the brain by inducing patient's finger exercise, and various rehabilitative techniques based on toys are being studied by researchers. In this study, we develop a smart cognitive rehabilitation block(LED blocks, 8x8 dot matrix blocks, speaker blocks, signage blocks, PWM switch blocks, 7-segment blocks), and establish a cognitive rehabilitation platform for patient management and develop cognitive rehabilitation contents.